2017
DOI: 10.18178/jocet.2017.5.1.343
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Self-Consumption Regulation for Photovoltaic Systems with Battery Banks in the Portuguese Residential Sector

Abstract: Abstract-Following recent trends in the developed countries, Portugal recently cut down the Feed-in tariffs for photovoltaic energy. They are now based on the Iberian market average (around 0.04€/kWh) while the final consumer electricity price is 0.16€/kWh. In this view, the PV system should be dimensioned for self-consumption since injecting into the grid produces less revenue. The motivation for the current work was to analyse the changes due to this new regulation, through the analysis of the economic feasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As far as PV technology gets technically and commercially mature, in Portugal, such as in most developed countries, the trend was to reduce Feed-intariffs (FiT) for renewable sources [7]. The FiT started with a value of 0.65€/kWh (DL 363/2007) and at present around to 0.09€/kWh while the electricity prices for the residential sector increases (the final consumer electricity price is 0.16 €/kWh) [8]. Taking into account this situation, generating electricity on-site on the household is more attractive than feeding into the grid.…”
Section: Introductionmentioning
confidence: 99%
“…As far as PV technology gets technically and commercially mature, in Portugal, such as in most developed countries, the trend was to reduce Feed-intariffs (FiT) for renewable sources [7]. The FiT started with a value of 0.65€/kWh (DL 363/2007) and at present around to 0.09€/kWh while the electricity prices for the residential sector increases (the final consumer electricity price is 0.16 €/kWh) [8]. Taking into account this situation, generating electricity on-site on the household is more attractive than feeding into the grid.…”
Section: Introductionmentioning
confidence: 99%
“…He argued that if the price of the PV systems falls down, it is reasonable to use the PV system as the primary source of energy for Nigeria when its average daily solar radiation is between 4 and 6 KW/m 2 /day [28]. Many other researchers investigated the potential usage of PV systems for different parts of the world like China, Portugal and so forth [29][30][31]. Considering so many investigations, it can be concluded that in many locations in the world energy can be supplied with the help of PV systems.…”
Section: Introductionmentioning
confidence: 99%